STRATEGI GURU DALAM MENGEMBANGKAN CINTA TANAH AIR SISWA PADA PEMBELAJARAN SEJARAH DI KELAS XI - Suraya, Fitriani; Sulistyarini, Sulistyarini; Noor, Agus Sastrawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to find out about "Teacher Strategies in Developing Love of theMotherland in History Subjects of Class XI Students of SMA Negeri 6 Pontianak". The research method used is descriptive method with a qualitative research form. The data sources of this study were History subject teachers and students of Class XI Science. Data collection techniques observation techniques, interviews, and documentation, while the data collection tools used observation guides, interview guides, anddocumentation. The analysis in this study wasÂ  in a descriptive qualitative manner using 6 informants. The results of this that the strategy implemented carried out through learning activities by implementing role models, routine activities, conditioning activities and spontaneous activities. The strategy a good impact on student character with supporting factors from the teacher, school and motivation of students. There inhibiting a sense of love of the motherland in students difficult at the time of application and also things that are technical. The teacher's strategy in developing homeland love in the history subjects of class XI of SMA Negeri 6 Pontianak has been considered good.Keywords: Teacher Strategy, Homeland Love, History